SOCIAL VALUES IN TERE LIYE’S NOVEL HUJAN - Ika Wulandari; Purwarno Purwarno; M. Manugeren (Universitas Islam Sumatera Utara (UISU), 2018)
This research focuses on social values reflected in Tere Liye’s novel entitled Hujan. The research is aimed at revealing the kinds of social values in the novel. Soekanto (1982) states that social value is a concept in a man in a society about what is considered good and bad, beautiful or not and right or wrong. In this reserach, the theory of social values is proposed by Djamaris (1993) who claims that social values can be divided into ten kinds namely Affection, Forgiveness, Obedience, Courtesy, Deliberation, Mutual Cooperation, Sympathy and Empathy, Wisdom, Respecting Others, and Responsibility The method used in this research is descriptive qualitative and structural objective approach developed by Semi (1985). The research result shows that seven kinds of social values are found in the novel: Love, Forgiveness, Obedience, Mutual Cooperation, Wisdom, Respecting Others, and Responsibility. However, the most dominant social value found in the novel is affection; which is reflected mainly from parents and friends.